Loyalty and liberation: The political life of Zephaniah Moyo - Alexander, J (Taylor and Francis, 2017)
Southern African liberation movements in and out of power have been bedeviled by a politics in which loyalties are uncertain and histories of division cannot easily be shed. I use the story of Zephaniah Moyo, who was over his lifetime both loyal to and accused of treachery by all three armed adversaries in Zimbabwe’s liberation struggle, to argue that the disruptive power of histories of division cannot be reduced to the binaries of loyalty and betrayal, heroes and traitors. Its enduring disruptiveness is rooted in contestations over the purposes of political lives and the complex content of loyalties that are sedimented in institutions, ideas and individual agendas over time and across space. Moyo’s narrative allows a deep excavation of these histories. He locates his loyalty in a vision of political order, founded in an unlikely embrace of Rhodesian bureaucracy and professionalism, and reified in the governance of the military camps in Zambia and in the violent state-making of 1980s Zimbabwe. While his is an individual story, its telling is situated in a collective critique of arbitrary rule and the claims of a heroic nationalism, and it describes a specifically Zimbabwean history of bureaucracy as political ideal. This biographical excavation allows a reevaluation of the possibilities – often foreclosed – of the political project of liberation.